The role of pre-existing social ties in jihadi-salafist radicalization: the case of Spain - Tovar i Velasco, Marina (Análisis Jurídico - Político, 2022)
This research paper analyses how pre-existing social ties influence in the Jihadi-Salafism radicalization processes from the theoretical point of view and provides a practical approach by studying data on this matter applied to Spain. The empirical-descriptive methodology will consist firstly on gathering information from the literature on jihadist radicalization and network formations and secondly, using El Cano’s database of Jihadists in Spain (BDEYE) data from 2001 to 2018 to observe how pre-existing social ties and radicalization modalities in the two periods evolve. Our two research questions: (1) Are social networks, and specifically, pre-existing social ties significant in the process of jihadi-Salafism radicalization in Spain? And (2) As the Internet and social media platforms become prominent in the second period of study, will the role of pre-existing social networks still be relevant? will guide our research. In our case study will observe the data and test our hypothesis, “social networks, especially pre-existing social ties, are essential in adopting radical jihadist beliefs in Spain in the two periods". In Spain, when pre-existing social ties existed, friendship and kinship allowed individuals to engage in radicalization processes. The low cost of maintaining social media platforms and websites with the diffusion of jihadist propaganda have let social media channels increase their importance, changing trends in the two periods studied. However, the change in pattern does not decrease the importance of pre-existing social ties to virtual communities as the mixed and offline modality in the second period gathered 71,9% of individuals, proving that pre-existing social ties are a crucial variable.